Age-Related Features of the Relationship Between Sociometric Status and Mental States of Children - Svetlana G. Krasnova (Развитие образования, 2020)
The article is devoted to identifying the relationship between mental states and the sociometric status of children in a group at preschool educational institutions. In is noted that determining the relationship between mental states and status characteristics is important in understanding the mechanisms of children's development in ontogenesis and is associated with the need to ensure emotional well-being and successful socialization of a child. The psychodiagnostic methods, adequate research goals, methods of statistical processing of experimental data (criterion r – Pearson correlation coefficient, multifunctional difference criterion φ – Fisher’s angular transformation) were applied during investigational study. The results of correlation analysis are presented in the article. The analysis of correlations allowed to identify pervasive and specific, peculiar only to a certain age stage of development, negative and positive mental states of children, depending on their status characteristics. The data obtained in the course of the study significantly enrich the existing ideas about the characteristics of preschoolers with different sociometric status. It is concluded that the presence of statistically significant differences in the frequency of manifestations of mental states allowed to determine the specifics of socio-psychological features of the states of children of different status groups. The need to take into account these ideas is associated with the fact that mental formations formed at this age are stable and persist for many years, determining the further development of the child. Negative states, creating a vicious circle, can have a negative impact on the formation of the child's relationship system in a group of peers.